Mudarabah di BSI Cabang Kota Ternate (Bank Sebagai Mudharib, Metode Bagi Hasil & Bank Sebagai Agent Investasi - Lestari, Sugi Indah; Umasugi, Nirwan (Jurnal Ilmiah Wahana Pendidikan, 2026)
The mudarabah contract is one of the main instruments in Islamic banking that functions to encourage real sector financing thru a profit-sharing mechanism and the principle of risk sharing. However, in practice, the implementation of this contract still faces challenges related to investment risk management and the protection of customer interests. This study aims to analyze the implementation of the mudarabah contract at BSI Ternate City Branch, focusing on the bank's role as the mudharib, the profit-sharing mechanism, and the bank's function as an investment agent. This research also examines risk management strategies and supervisory systems in improving the effectiveness of real sector financing. The research method used is a qualitative method with a literature study approach. Data were obtained from Islamic banking regulations, fatwas from the National Sharia Council–MUI, Islamic accounting standards, official reports from Bank Syariah Indonesia, as well as relevant and up-to-date scientific journal articles. Data analysis was conducted descriptively and analytically. The research results indicate that BSI Ternate City Branch implements the mudarabah contract by setting a profit-sharing ratio agreed upon at the beginning of the contract and adjusted to the characteristics of the business. Investment risk management is carried out thru business feasibility analysis, periodic monitoring, supervision by the Sharia Supervisory Board, and financing restructuring mechanisms. The integration of profit-sharing mechanisms and supervisory systems has proven to increase the effectiveness of real sector financing by encouraging the use of funds in productive businesses, improving transparency, and maintaining a balance of interests between banks and customers.